2020
DOI: 10.1136/bmjresp-2020-000593
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal density of respiratory viruses in childhood pneumonia in a highly vaccinated setting: findings from a case–control study

Abstract: BackgroundDetection of pneumonia-causing respiratory viruses in the nasopharynx of asymptomatic children has made their actual contribution to pneumonia unclear. We compared nasopharyngeal viral density between children with and without pneumonia to understand if viral density could be used to diagnose pneumonia.MethodsNasopharyngeal swabs (NPS) were collected from hospitalised pneumonia cases at Princess Margaret Hospital (PMH) and contemporaneous age-matched controls at PMH outpatient clinics and a local imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Pathogen density in the nasopharynx could provide additional information and may further aid in distinguishing asymptomatic from symptomatic infections [ 45 ]. We found that the mean CT values were lower in all of the viruses detected in the cases with the exception of coronaviruses and human rhinoviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogen density in the nasopharynx could provide additional information and may further aid in distinguishing asymptomatic from symptomatic infections [ 45 ]. We found that the mean CT values were lower in all of the viruses detected in the cases with the exception of coronaviruses and human rhinoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies from sub-Saharan Africa reported higher nasopharyngeal viral density in LRTIs cases compared with non-LRTI controls [ 14 19 ]. For some viruses, increased nasopharyngeal viral load has been associated with the clinical severity of LRTIs in children [ 45 ].…”
Section: Discussionmentioning
confidence: 99%